Gated photochromic molecules with AIEgen: turn-on the photochromism with an oxidation reagent. Issue 33 (22nd May 2018) - Wang, Leyu; Yu, Tao; Xie, Zongliang; Ubba, Eethamukkala; Zhan, Tianya; Yang, Zhiyong; Zhang, Yi; Chi, Zhenguo
Abstract : Gated photochromic molecule: switchable photochromic materials with AIEgen were achieved. Oxidation reagents act as gates to switch the photochromic properties. Abstract : A couple of gated photochromic molecules TrPEP and TrPEPO with AIEgen have been rationally designed and synthesized. No photochromism is detected for TrPEP whilst TrPEPO shows obvious photochromic properties in the solution state. By adding equimolar H2 O2 aqueous solution to the TrPEP solution, the photochromic properties would be quickly turned on. The oxidation reagent acts as a gate to switch the photochromic properties by switching the triphenylphosphine group to a triphenylphosphine oxide group. Both TrPE and TrPEO display typical AIE phenomena. Different intensive emission bands with the emission maxima of 500 nm and 455 nm are detected before (TrPEP) and after (TrPEPO) oxidization in solid states. Combining the AIEgens, photochromic ON/OFF states can be easily indicated by the different emission colors in the solid state. Single crystal analyses and TD-DFT calculations were carried out to further investigate the photophysical and photochromic properties of these compounds. These new triphenylethylene derivatives provide a new strategy to achieve gated photochromic materials with simple chemical structures and gate indicators.